Litera-Rua: a cultura da periferia em Capão Pecado, de Ferréz - Darlan Santos; Jacques Fux (Estudos de Literatura Brasileira Contemporânea)
This article aims to tell the possibility of expression in contemporary society, by those who live on the margins of the society, condemned to residual life and nar- ratives. From this standpoint, we study the book Capão Pecado (2000), by Ferréz, presenting the voice of the subaltern and the marginal culture, specifically, in the so-called “Litera-Rua”.